FACTORS CONTRIBUTING TO THE PREVALENCE OF MALARIA AMONG CHILDREN UNDER FIVE YEARS ATTENDING HEALTH CARE AT ST ELIZABETH MAGALE HEALTH CENTER IV, NAMISINDWA DISTRICT. A CROSS-SECTIONAL STUDY. - Jude Moya; Lydia Anywar (Student's Journal of Health Research, 2023)
Introduction:  Malaria remains a major public health problem associated with slow economic development and it accounts for 27.7% of deaths among children under the age of five in Uganda (MOH, NMCP 2014 - 2020). The study, therefore, seeks to determine the factors contributing to the prevalence of malaria among children under five years attending Health care at St Elizabeth Magale Health Centre IV, Namisindwa district. Methodology:  A cross-sectional study was carried out among 100 caregivers of children below five years in St Elizabeth Magale health center IV from December 2022 to January 2023. A self-administered questionnaire was completed and data were analyzed. Results:  The prevalence of malaria was high 39(39%) and the factors that were significant with malaria prevalence included: caregivers with little 5% knowledge about other signs/symptoms like convulsions, loss of appetite, and body weakness, 71% were unemployed. Almost half did not own ITNs and environmental factors showed 56% of garbage heaps presence and 54% reported wet /rainy season to be associated with increased cases of malaria among children below five years. Conclusion:  The prevalence of malaria was high and it was influenced by caregivers' knowledge about malaria signs and symptoms, level of education, employment status, ownership of ITNs, garbage heaps, and season of the environment. Recommendations:  The study recommends the need for more awareness campaigns on malaria spread, clinical features, prevention through mass media (electronic and print media), markets, house-to-house sensitization, and traditional and religious leaders. The people should translate their good awareness of malaria into good preventive practices.  Furthermore, the study recommends more initiatives to be taken toward income-generating activities among people. This will potentially improve access to interventions and proper timely treatment of malaria among children under five years.